Characteristics of hypertension in the last 16 years in high prevalence region of China and the attribute ratios for cardiovascular mortality - Wenlong Zheng; Xiaohe Wang; Xiaodan Xue; Wei Li; Lili Fan; Shuang Zhang; Changkun Li; Zhuo Wang; Meiqiu Xie; Peng Xin; Guohong Jiang (BMC, 2023)
Abstract Background Tianjin is one of the cities with the highest prevalence of hypertension in China and one of the first regions to develop community management of hypertension. Our aim was to analyze the characteristics of hypertension in the last 16 years, and estimate the population attributable fraction for cardiovascular mortality in Tianjin, China. Methods We compared the epidemiological characteristics of hypertension between 2002 and 2018 by analyzing data from the National Nutrition and Chronic Disease Risk Factor Survey. Subsequently, we obtained the cause-specific mortality in the same year from the Tianjin All Cause of Death Registration System (CDRS), and the population attributable fraction was used to estimate the annual cardiovascular disease (CVD) deaths caused by hypertension. Results In 2002 and 2018, the crude prevalence, awareness, treatment rate in diagnosed, control rate in treated, and overall control rate of hypertension were 36.6% and 39.8%, 36.0% and 51.9%, 76.0% and 90.1%, 17.4% and 38.3%, 4.8% and 17.9%, respectively (P < 0.05). The mean SBP for males between the ages of 25 and 50 was significantly higher in 2018 than in 2002. The number of CVD deaths attributed to hypertension was 13.8 thousand in 2002 (account for 59.1% of total CVD deaths), and increased to 21.7 thousand in 2018 (account for 58.8% of total CVD deaths). The population attributable fraction have increased in the age groups of 25-44 and 75 and above, and decreased in the age group of 45-74 from 2002 to 2018. Conclusions Compare to 2002, the proportion of CVD deaths attributed to hypertension remains high, particularly among younger and older people, despite a very significant increase in treatment and control rates for hypertension in 2018.